2008
DOI: 10.3347/kjp.2008.46.4.235
|View full text |Cite|
|
Sign up to set email alerts
|

Sympatric Distribution of Three Human Taenia Tapeworms Collected between 1935 and 2005 in Korea

Abstract: Taeniasis has been known as one of the prevalent parasitic infections in Korea. Until recently, Taenia saginata had long been considered a dominant, and widely distributed species but epidemiological profiles of human Taenia species in Korea still remain unclear. In order to better understand distribution patterns of human Taenia tapeworms in Korea, partial nucleotide sequences of mitochondrial cox1 and ITS2 (internal transcribed spacer 2) were determined, along with morphological examinations, on 68 Taenia sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Most of the formalin-preserved samples yielded weak or no PCR amplification, but secondary PCR using the PCR products obtained from the first round of PCR amplifications as a template produced made it possible to use PCR product for direct sequencing. The results clearly indicate that all 3 human Taneia tapeworms are distributing together in Korea [14]. T. asiatica is dominating in Korea and the local Korean peoples get this tapeworm by eating undercooked livers and visceral organs of pigs.…”
Section: The Republic Of Koreamentioning
confidence: 87%
See 2 more Smart Citations
“…Most of the formalin-preserved samples yielded weak or no PCR amplification, but secondary PCR using the PCR products obtained from the first round of PCR amplifications as a template produced made it possible to use PCR product for direct sequencing. The results clearly indicate that all 3 human Taneia tapeworms are distributing together in Korea [14]. T. asiatica is dominating in Korea and the local Korean peoples get this tapeworm by eating undercooked livers and visceral organs of pigs.…”
Section: The Republic Of Koreamentioning
confidence: 87%
“…The epidemiological profile of these Taenia species in humans remained unclear up to recent until Jeon et al [14] reported distribution pattern of Taenia tapeworms in Korea. Morphological examination as well as partial nucleotide sequences of mitochondrial cox1 and ITS2 (internal transcribed spacer 2) were analyzed for 68 specimens from university or institute museum collections deposited since 1935 [14]. The specimens were identified as 3 T. solium, 51 T. asiatica, and 14 T. saginata (Table 1) [11,14].…”
Section: The Republic Of Koreamentioning
confidence: 99%
See 1 more Smart Citation
“…4 Apparently, there are no reasons why globalization should have excluded T. asiatica , because it is a tapeworm with cosmopolitan hosts with migratory movements, and it is not a sporadic parasite being more common than T. solium or T. saginata . 5,6 Concerning human cysticercosis, WHO/FAO/OIE maintain that T. asiatica probably does not cause this disorder because of its molecular similarities with T. saginata , the species that does not cause it. 7 However, T. saginata does not produce pig cysticercosis but T. asiatica does, because the pig and not cattle is its intermediate host despite these similarities.…”
Section: Letters To the Editor Diagnosis Of Human Cysticercosis And Tmentioning
confidence: 99%
“…T. asiatica is distributed in Asian countries, including Korea, China, Japan, Taiwan, Thailand, Vietnam, and the Philippines [3]. In Korea, this tapeworm is the dominant species and widely distributed, including Jeju-do (Province) [4]. The diagnosis of T. asiatica and differential diagnosis from other human Taenia tapeworms have been developed.…”
Section: Introductionmentioning
confidence: 99%